The bang for its buck: Impacts of 40 years of policy research at IFPRI - Hazell, Peter B. R.; Slade, Roger (International Food Policy Research Institute, 2015)
As the International Food Policy Research Institute celebrates its 40th anniversary, it is an appropriate time for the Institute and its key stakeholders to take stock of what is known about its policy influence and impact over the years. Has IFPRI been a worthwhile undertaking? What does available evidence tell us about how IFPRI might achieve even greater policy influence and impact in the future? This brief draws on a forthcoming paper1 that uses external sources of evidence to address these questions, including citations data, external program and management reviews commissioned by CGIAR, and a series of independently conducted impact assessment studies of many of IFPRI’s research programs and projects. While this body of evidence lacks scientific rigor, it does reflect the views of external experts based on careful study of the available evidence